2022
DOI: 10.3390/vaccines10010121
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Socioeconomic Disparities in COVID-19 Vaccine Second-Dose Completion Rates in the United States

Abstract: Although COVID-19 vaccination plans acknowledge a need for equity, disparities in two-dose vaccine initiation have been observed in the United States. We aim to assess if disparity patterns are emerging in COVID-19 vaccination completion. We gathered (n = 843,985) responses between February and November 2021 from a web survey. Individuals self-reported demographics and COVID-19 vaccination status. Dose initiation and completion rates were calculated incorporating survey weights. A multi-variate logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
6
16
0
Order By: Relevance
“…In addition to transportation barriers, particularly for residents living in rural communities, our regression results confirm the role of socioeconomic factors that reflect economic insecurity, particularly educational attainment, that also affects income earnings. These findings complement the existing literature that focuses on social inequity in COVID-19 vaccinations [ 6 , 7 , 8 , 9 , 11 ]. On the other hand, our empirical results contradict earlier studies that reported challenges facing racial/ethnic minorities in the U.S. [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition to transportation barriers, particularly for residents living in rural communities, our regression results confirm the role of socioeconomic factors that reflect economic insecurity, particularly educational attainment, that also affects income earnings. These findings complement the existing literature that focuses on social inequity in COVID-19 vaccinations [ 6 , 7 , 8 , 9 , 11 ]. On the other hand, our empirical results contradict earlier studies that reported challenges facing racial/ethnic minorities in the U.S. [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 80%
“…The objective of our empirical work is to evaluate the sources of under-vaccination during the COVID-19 pandemic. In light of the existing literature that emphasizes the role of socioeconomic and demographic factors [ 6 , 7 , 8 , 10 , 11 , 12 , 13 ], we consider the various components that make up the U.S. Centers for Disease Control and Prevention’s [ 26 ] Social Vulnerability Index (SVI). The SVI is aimed at helping public health officials and policymakers better prepare for disease outbreaks and other disasters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of the poorest part of the population from the social contract could lead to a diminished sensitivity towards the national solidarity dimension of vaccination, strongly emphasised in the public discourse on prevention in France. The low rates of vaccination among the most deprived, also found in a US survey [9], probably also relates to the fact that they generally have poor access to healthcare than others for given needs. [12] Our results underline the need to develop outreach strategies targeting the poorest, the least educated people, and the racialised minorities, as recommended by Hanif back in 2020.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3] Making Covid-19 vaccines available does not necessarily lead to a very large population vaccine coverage, as shown by the percentages of people who are still not vaccinated in Western countries [4], even when these vaccines are free. Recent studies in the UK, in the US and in Norway [5][6][7][8][9][10] have shown that the most socially disadvantaged and racialised social groups are the least vaccinated. In light of their high risk of infection and mortality from Covid-19 [1], it appears all the more important to understand why they are less likely to be reached by Covid-19 vaccine programmes.…”
Section: Introductionmentioning
confidence: 99%